2017
DOI: 10.5455/medarh.2017.71.69-71
|View full text |Cite
|
Sign up to set email alerts
|

Mini Asymmetric Radial Keratotomy and Corneal Cross-linking for the Treatment of a Bilateral Stage IV Keratoconus in a 14-year-old Child

Abstract: Aim:To present the case of a 14-year-old boy with bilateral stage IV keratoconus, treated with a combined MARK + CXL intervention, without the need for a corneal transplantation.Results:The left eye displays considerable improvements, with a follow-up of 13.5 years: Kmax is decreased by 5.53 D, Kmed is decreased by 1.95 D and thinnest pachymetry is increased by 106 µm. The right eye shows equally remarkable parameters, with a follow-up of 9.5 years: Kmax is decreased by 8.16 D, Kmed is decreased by 0.38 D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The last option in management too thin cornea is completely replacing the all layer (penetrating keratoplasty) or partial layers (lamellar keratoplasty) with new healthy donor tissue (5) . Some studies reported that exposure of guinea pigs to ultraviolet rays A develops nuclear cataract (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The last option in management too thin cornea is completely replacing the all layer (penetrating keratoplasty) or partial layers (lamellar keratoplasty) with new healthy donor tissue (5) . Some studies reported that exposure of guinea pigs to ultraviolet rays A develops nuclear cataract (6) .…”
Section: Introductionmentioning
confidence: 99%
“…According to recent literature, the prevalence and annual incidence of KC are 1:375 and 1:7,500, respectively, which are five- to tenfold higher than those in previous report [2]. Although many established therapies, such as rigid gas-permeable contact lenses and corneal transplantation, are effective in improving KC patient vision, corneal cross-linking (CXL) was the only minimally invasive treatment to improve corneal biomechanical property and halt the progression of KC [35].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a slight degree of corneal flattening with the ‘epi-off’ (Dresden protocol) technique, however, it does not significantly improve a patient's visual acuity [14], a condition that has led to a number of CXL-combined procedures. Combined protocols discussed in the medical literature include CXL paired with photorefractive keratectomy (PRK) (Athens protocol) [15], femtosecond laser-assisted in situ keratomileusis (FemtoLASIK) [16], ICRS [17], phakic intraocular lenses [18], CKP [19], and MARK [20]. The latter combined intervention, the ‘Rome protocol,’ was the focus of this study, the aim of which was to investigate the effectiveness of this protocol for disease stabilization and improvement of visual acuity based on long-term follow-up data.…”
mentioning
confidence: 99%